2016
DOI: 10.1097/brs.0000000000001484
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Laminoplasty with Interlaminar Lumbar Instrumented Fusion (ILIF) for Lumbar Stenosis with or Without Grade 1 Spondylolisthesis

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The results obtained at the end of Phase II of the study (36-m after surgery) indicated the efficacy of spinal fixation using percutaneous screw and rod spinal fixation, alone or as a part of the 3-in-1 procedure for management of FBSS patients as evidenced by the maintained significant reduction of pain and disability scores till 36-m PO in comparison to preoperative scores. These findings supported the previous studies that documented the long-term improvement of ODI and pain scores after instrumented fusion of FBSS patients [31][32][33][34][35]. The 3-in-1 procedure maintained significantly lower ODI and pain scores in comparison to preoperative scores and to the 36-m scores of patients had PSRF only.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained at the end of Phase II of the study (36-m after surgery) indicated the efficacy of spinal fixation using percutaneous screw and rod spinal fixation, alone or as a part of the 3-in-1 procedure for management of FBSS patients as evidenced by the maintained significant reduction of pain and disability scores till 36-m PO in comparison to preoperative scores. These findings supported the previous studies that documented the long-term improvement of ODI and pain scores after instrumented fusion of FBSS patients [31][32][33][34][35]. The 3-in-1 procedure maintained significantly lower ODI and pain scores in comparison to preoperative scores and to the 36-m scores of patients had PSRF only.…”
Section: Discussionsupporting
confidence: 90%
“…Cuellar et al performed a prospective multicenter study evaluating interlaminar lumbar instrumented fusion, which is a subtype of ISF. 104 Thirty-seven patients with single level degenerative lumbar stenosis were treated with lumbar decompression using a laminoplasty procedure followed by insertion of an allograft bone block and interspinous stabilization/fixation device. Follow-up was up to 24 months; 33 patients met the endpoint criteria (ODI and ZCQ) at 2 years.…”
Section: Interspinous Fusionmentioning
confidence: 99%
“…Another multicenter, RCT compared ISF with decompression to decompression with pedicle screw fusion. 104 Subjects with moderate-to-severe lumbar stenosis were included and followed for 5 years. Composite endpoints included ODI, repeat surgery, further lumbar injections, or adverse events.…”
Section: Interspinous Fusionmentioning
confidence: 99%
“…com/CJP/A846), while 32 (9.7%) reported that they tracked opioid use. However, of these 32, only 21 studies (6.4% of all studies) 41,[43][44][45][46][47]49,52,53,[56][57][58][60][61][62][63]65,[69][70][71][72] specifically reported opioid use out to at least 6 months (Table 2). Eleven of the 329 studies 42,48,50,51,54,55,59,64,[66][67][68] tracked opioid use before surgery or immediately after surgery but did not track opioids out at least 6 months.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%